PENGARUH BRAND TRUST, DIVERSIFIKASI PRODUK DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN STARBUCKS DI PEKANBARU - Naldi Wija Agus; Jushermi Jushermi; Taufiqurrahman Taufiqurrahman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine, (1) the effect of brand trust on purchasing decisions, (2) the effect of product diversification on purchasing decisions, (3) the influence of lifestyle on purchasing decisions. The object of this research is all Starbucks consumers who have bought Starbucks products who are domiciled in Pekanbaru. Data analysis in this study used Multiple Linear Regression using SPSS. Based on the test results, brand trust has a positive and significant effect on purchasing decisions, product diversification has a positive and significant effect, lifestyle has a positive and significant effect.Keywords: Brand Trust, Product Diversification, Lifestyle, Purchase Decision